The Role of the Convergent Discovery Teaching Style in Developing Fundamental Soccer Passing Skills: A Systematic Literature Review - Irfan, M.; Harahap, Nur Kholilah; Manik, Fajar; Situmorang, Ricard; Pratama, Muhammad Arkan; Siregar, Togu Muzaqi; Kartika, Adinda Tri; Sianturi, Christin Rani; Br Perangin-Angin, Reka Kristi; Br Depari, Emia Kataraina (INSPIRETECH GLOBAL INSIGHT & Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2026)
Objectives: This systematic literature review examines the role of the Convergent Discovery Teaching Style (CDTS) in developing fundamental soccer passing skills among youth and adolescent players. The study aims to synthesize empirical evidence regarding the effectiveness of CDTS compared to traditional directive teaching methodologies in sport physical education and coaching contexts. Methods: A systematic search was conducted across four electronic databases (Web of Science, Scopus, ERIC, and SPORTDiscus) from inception to December 2024 following the PRISMA 2020 guidelines. Studies were included if they: (1) investigated the application of CDTS or inquiry-based teaching styles; (2) targeted soccer passing skills as primary or secondary outcomes; (3) were published in peer-reviewed journals; and (4) included empirical data. From an initial pool of 430 records, 25 studies met the eligibility criteria and were included in the final analysis. Results: The analysis of 25 eligible studies (n total = 1,284 participants) revealed that CDTS was consistently associated with statistically significant improvements in short passing accuracy, long passing consistency, decision-making under pressure, and skill retention compared to command-style approaches. Effect sizes ranged from moderate to large (Cohen's d = 0.54–1.12). CDTS also demonstrated superior outcomes in cognitive engagement, tactical understanding, and intrinsic motivation among learners. Conclusion: CDTS emerges as a pedagogically sound and effective approach for developing soccer passing skills in youth populations. Its emphasis on guided problem-solving aligns with cognitive- constructivist frameworks of motor learning. Physical educators and coaches are encouraged to integrate CDTS within structured progression models. Future research should explore its long-term retention effects, optimal implementation dosage, and application across diverse cultural and competitive contexts.